Defect properties of albite: a combined empirical potential and density functional theory study - Lowitzer, S.; Wilson, D.; Winkler, B.; Milman, V.; Gale, Julian (Springer-Verlag, 2008)
Knowledge of the defect properties of Lunar and Mercurian minerals has recently become important, with the advent of models which attempt to explain the formation of the thin exosphere of these celestial bodies. Here, we have calculated the formation energies of sodium and oxygen vacancies in the mineral albite (NaAlSi3O8), as well as the Schottky defect energy for the removal of a Na2O unit. We have employed both the supercell and Mott-Littleton approaches, using Kohn-Sham density functional theory and classical interatomic potential methods. As well as reporting the defect energies and structures, we comment upon the relative merits of the methods used.